Nickel aluminide coating as catalyst in steam methane reforming microreactor - Sarwani, Muhamad Khairul Ilman (2017)
The catalyst deposition in microreactor for steam methane reforming (SMR) on a micro-scale poses new opportunities due to lack of literatures. Using plate-type catalyst as a basis, a foundation work on the preparation and analysis of catalyst deposition, specifically by dip coating (DC) method was conducted. This study which to deposit nickel aluminide catalyst on stainless steel 304 (SS304) substrate plates with different roughness and DC withdrawal speed has been conducted. Analysis of calcination temperatures on nickel aluminide thin film, followed by characterization of nickel aluminide thin film, then tested with SMR yield were performed. The studied parameters used DC withdrawals speed of 40, 80, 120, 160 and 200 mm/min. Next, calcination temperatures of 300, 400, 500 and 600°C for 90 minutes each were tested. All deposited substrates were characterized using Atomic Force Microscopy (AFM) and X-ray Diffraction (XRD). Polished substrate produced average surface roughness 0.18, 0.13 and 0.09 μm. The Atomic Force Microscopy results showed that film thickness and roughness are proportional to the withdrawal speed, however, the inverse effect on sol-gel adhesion on the substrate due to gravitational drag force limitation. Substrate with roughness of 0.13 μm and dip coating withdrawal speed 160mm/min shows the highest coating thickness and surface roughness. The nickel aluminide catalyst film‘s average roughness (Ra) and ten-point mean height (Rz) had increased proportionally when the calcination temperature increases from 300 to 500°C, but not at 600°C. In addition, higher calcination temperature produces more Nickel aluminide compared to lower calcination temperature. The deposited catalyst was activated using hydrogen and then tested in an SMR microreactor. Results showed that using this catalyst, a mixture of steam and methane were reformed to hydrogen and carbon monoxide at temperature between 550°C and 650°C. Thus, it is confirmed that the method applied in this study was able to produce a functioning nickel aluminide catalyst for SMR microreactor.